1131 The Integration of Cardiothoracic Practical Skills Workshop in The Undergraduate Medical School Curriculum and Its Impact on Promoting Interest in Cardiothoracic Surgery. (12th October 2021) - Raja, M S; Dhuga, Y; Modi, S; Nagasubramony, A; Sood, S; Ahmed, I
Abstract: : Recently, a downward trend is seen in undergraduates wishing to pursue a career in cardiothoracic surgery(CTS). This is partly due to lack of clinical exposure and limited teaching during the undergraduate years; the focus being on cardiac ad vascular pathology. Aim: Assess if WETLAB workshop encourages the engagement of medical students in CTS surgery Method: We hosted a cardiac WETLAB workshop, led by a consultant cardiothoracic surgeon. Attendees were taught how to carry out an end-to-side anastomosis on animal tissue. We used pre-and -post exposure questionnaires composed of 10 items to assess the ability of the workshop to improve undergraduate interest in cardiothoracic surgery. The questionnaire included questions around students' interest in the speciality, previous exposure to the speciality and whether students want to pursue a career in the speciality. Results: Out of the 12 attendees, 10 completed both questionnaires. The workshop was well received with the overall satisfaction of 9.64 out of 10. It significantly increased respondents' interest in CTS(z=-0.06, p = 0.01) but did not show any significant difference in encouraging them to pursue surgery. 100% of respondents agreed that specialised practical workshops should be incorporated within the medical school curriculum and that if the opportunity arises, they will attend another in the future. Conclusions: Specialised practical workshops have the potential to play a significant role in the medical school curriculum in order to enhance exposure to the field of cardiothoracic surgery. This may lead to a positive impact on the number of doctors wishing to pursue this speciality in the future.